Flightless I over‐expression impairs skin barrier development, function and recovery following skin blistering. Issue 5 (5th February 2014) - Kopecki, Zlatko; Yang, Gink N; Arkell, Ruth M; Jackson, Jessica E; Melville, Elizabeth; Iwata, Hiroaki; Ludwig, Ralf J; Zillikens, Detlef; Murrell, Dedee F; Cowin, Allison J
Abstract Development of an intact epidermis is critical for maintaining the integrity of the skin. Patients with epidermolysis bullosa (EB) experience multiple erosions, which breach the epidermal barrier and lead to increased microbial colocalization of wounds, infections and sepsis. The cytoskeletal protein Flightless I (Flii) is a known regulator of both development and wound healing. Using Flii+/−, WT and FliiTg/Tg mice, we investigated the effect of altering Flii levels in embryos and adult mice on the development of the epidermal barrier and, consequently, how this affects the integrity of the skin in EB. Flii over‐expression resulted in delayed formation of the epidermal barrier in embryos and decreased expression of tight junction (TJ) proteins Claudin‐1 and ZO‐2. Increased intercellular space and transepidermal water loss was observed in FliiTg/Tg adult mouse skin, while FliiTg/Tg keratinocytes showed altered TJ protein localization and reduced transepithelial resistance. Flii is increased in the blistered skin of patients with EB, and over‐expression of Flii in experimental EBA showed impaired Claudin‐1 and ‐4 TJ protein expression and delayed recovery of functional barrier post‐blistering. Immunoprecipitation confirmed Flii associated with TJ proteins and in vivo actin assays showed that the effect of Flii on actin polymerization underpinned the impaired barrier function observed in FliiTg/Tg mice. These results therefore demonstrate an important role for Flii in the development and regulation of the epidermal barrier, which may contribute to the impaired healing and skin fragility of EB patients. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd